YES * Step 1: FromIts YES + Considered Problem: Rules: 0. f(A,B,C) -> g(A,1,0) True (1,1) 1. g(A,B,C) -> g1(-1 + A,B,B) [-1 + A >= 0] (?,1) 2. g1(A,B,C) -> g(A,B + C,C) True (?,1) 3. g(A,B,C) -> h(A,B,C) [0 >= A] (?,1) 4. h(A,B,C) -> h(A,-1 + B,C) [-1 + B >= 0] (?,1) Signature: {(f,3);(g,3);(g1,3);(h,3)} Flow Graph: [0->{1,3},1->{2},2->{1,3},3->{4},4->{4}] + Applied Processor: FromIts + Details: () * Step 2: Decompose YES + Considered Problem: Rules: f(A,B,C) -> g(A,1,0) True g(A,B,C) -> g1(-1 + A,B,B) [-1 + A >= 0] g1(A,B,C) -> g(A,B + C,C) True g(A,B,C) -> h(A,B,C) [0 >= A] h(A,B,C) -> h(A,-1 + B,C) [-1 + B >= 0] Signature: {(f,3);(g,3);(g1,3);(h,3)} Rule Graph: [0->{1,3},1->{2},2->{1,3},3->{4},4->{4}] + Applied Processor: Decompose NoGreedy + Details: We construct a looptree: P: [0,1,2,3,4] | +- p:[1,2] c: [1,2] | `- p:[4] c: [4] * Step 3: CloseWith YES + Considered Problem: (Rules: f(A,B,C) -> g(A,1,0) True g(A,B,C) -> g1(-1 + A,B,B) [-1 + A >= 0] g1(A,B,C) -> g(A,B + C,C) True g(A,B,C) -> h(A,B,C) [0 >= A] h(A,B,C) -> h(A,-1 + B,C) [-1 + B >= 0] Signature: {(f,3);(g,3);(g1,3);(h,3)} Rule Graph: [0->{1,3},1->{2},2->{1,3},3->{4},4->{4}] ,We construct a looptree: P: [0,1,2,3,4] | +- p:[1,2] c: [1,2] | `- p:[4] c: [4]) + Applied Processor: CloseWith True + Details: () YES